D-Galactose Induces Chronic Oxidative Stress and Alters Gut Microbiota in Weaned Piglets - Han, Hui; Liu, Zemin; Yin, Jie; Gao, Jing; He, Liuqin; Wang, Chenyu; Hou, Ruoxin; He, Xingguo; Wang, Guoqiang; Li, Tiejun; Yin, Yulong (Frontiers in Physiology, 2021)
Oxidative stress commonly occurs in pig production, which can severely damage the intestinal function of weaned piglets. This study was conducted to investigate the effects of D-galactose with different levels used to induce chronic oxidative stress on growth performance, intestinal morphology and gut microbiota in weaned piglets. The results showed that addition of 10 and 20 g/kg BW D-galactose reduced average daily gain and average daily feed intake from the first to the third week. 10 g/kg BW D-galactose increased the concentration of serum MDA at the second and third week. 10 g/kg BW D-galactose significantly influenced the jejunal and ileal expressions of GPx1, CAT1, and MnSOD. The results of 16S rRNA sequencing showed that compared with the control, 10 and 20 g/kg BW D-galactose significantly decreased the relative abundance of Tenericutes, Erysipelotrichia, Erysipelotrichales, and Erysipelotrichaceae, while increased the relative abundance of Negativicutes, Selenomonnadales, and Veillonellaceae. The results indicated that treatment with 10 g/kg BW/day D-galactose for 3 weeks could induce chronic oxidative stress, reduce the growth performance and alter gut microbiota in weaned piglets.